(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
This research policy review examines the transformative journey of Union Christian College (UCC) from the pre-pandemic to the post-pandemic era. Despite facing significant challenges, UCC has demonstrated exceptional performance and commitment to sustaining its operations. The review highlights UCC’s achievements, including international partnerships, service-learning initiatives, blended instruction, accreditation success, and program expansion. Looking ahead, UCC’s goals and initiatives for the 2022-2027 term emphasize academic rationalization, graduate program expansion, community engagement, and technological innovation. The implications of UCC’s journey extend globally, showcasing the significance of academic excellence, research collaborations, and the holistic development of students. This research policy review provides valuable insights into UCC’s transformative efforts, serving as a model for educational institutions seeking to excel in a rapidly evolving landscape. Introduction Union Christian College (UCC) has undergone significant transformations from the pre-pandemic to the post-pandemic era, covering the administrative terms of 2017-2022 and 2022-2027. Despite facing various challenges during the previous term, UCC has demonstrated outstanding performance and commitment to sustaining its operations. In the current administrative term, UCC aims to focus on academic excellence, positive prophetic presence, and spirituality through its UCC @APPS agenda. This research policy review will outline the achievements and goals of UCC, highlighting the specific initiatives and strategies for the 2022-2027 term. Achievements and Measures of Outcome: During the 2017-2022 administrative term, UCC successfully implemented several measures to enhance its instruction, research, and extension programs. Key achievements include: International Partnerships: UCC established research partnerships with the Ascendens Asia Group and Singapore Institute of Multidisciplinary Professions, elevating its localized research dissemination and publications. This international collaboration enhances UCC’s global presence and research contributions. Service-Learning Asia Network: UCC became an institutional member of the Service-Learning Asia Network, emphasizing its commitment to community engagement and service-learning initiatives. Blended/Hybrid Instruction: UCC continued to utilize blended/hybrid instruction, ensuring flexibility and adaptability in response to changing educational needs. Regional Quality Assurance Team (RQAT) Commendation: UCC received a satisfactory commendation from the RQAT of the Commission on Higher Education (CHED) for all visited collegiate programs, demonstrating quality assurance and compliance. Limited Face-to-Face Approval: UCC obtained the approval of the local government unit (LGU) and CHED for the limited implementation of face-to-face classes and activities, facilitating a safe and conducive learning environment. Program Expansion: UCC obtained permits to operate new programs, such as BS Real Estate Management and BS Information System under the School of Business Sciences, ensuring program diversity and meeting industry demands. Consortium Agreements and Community Partnerships: UCC renewed its consortium agreement with PCU Manila, established partnerships with the City of San Fernando and the Institute of Social Order (ISO), and adopted Sta. Monica as its Adopted Barangay, strengthening collaborations for graduate programs and community engagement activities. Accreditation Achievements: UCC received level 2 five-year accreditation for several programs, including MAEd in Teacher Education, MAEd in Pre-School Education, Bachelor in Secondary Education, Bachelor in Elementary Education, and Bachelor of Science in Business Administration. Additionally, level 2 three-year accreditation was obtained for programs such as Bachelor of Science in Accountancy, AB Programs, Junior High School, Elementary, and Pre-School programs. The MAN program achieved level 1 three-year accreditation from its candidate status. Goals and Initiatives for the 2022-2027 Term: The 2022-2027 administrative term at UCC focuses on the UCC @APPS agenda, which aims to transform the institution into a top-notch center of higher learning with global outreach. The specific goals and initiatives for this term include: Academic Rationalization: UCC plans to rationalize academic and academic support departments to meet the evolving demands of the times, ensuring efficiency and effectiveness in delivering quality education. Graduate Program Expansion: UCC aims to increase the offerings of its Graduate School programs in collaboration with the Philippine Christian University (PCU), focusing on the Transnational & Globalization Program and the development of an MS in Nursing Program. Accreditation and Program Expansion: UCC aims to sustain the high accreditation status of the Nursing Program and secure reaccreditation for Level IV. Additionally, partnerships with the Polytechnic College in La Union (PCLU) will expand the school’s capacity to cater to students, particularly in the BS Nursing program. Furthermore, the introduction of new programs such as Bachelor of Culture and Arts Education (BCAEd) and TESDA/short-term programs in the School of Health Sciences will enrich program offerings. Certification Programs and Business Sciences: UCC plans to intensify the offering of certification programs in Teaching and Early Childhood Education (ECE) under the School of Education, Arts, and Sciences (SEAS). The School of Business Sciences (SBS) will reinforce new programs in BS Real Estate Management (BE REM) and BS Information System (BS IS), aligning with industry demands. Campus Expansion and Outreach: UCC aims to operationalize the Union Christian College, Rosario Annex, under the supervision of the Basic Education Department, enhancing the institution’s presence and accessibility. Furthermore, UCC seeks to expand research engagements with Ascendens Asia Singapore and other partners, advancing its reputation as a research-oriented institution. Marketing, Promotion, and Alumni Affairs: UCC plans to advance its marketing, promotion, and alumni affairs programs by establishing the Center for Research Development, Marketing, and Alumni Affairs (CReDMAA), ensuring effective communication and engagement with stakeholders. Community Engagement and Technological Innovation: UCC aims to strengthen its community engagement programs through the Center for Community Engagement, Technological Innovation, and Development (CCETID), fostering partnerships and enhancing the impact of outreach activities. Additionally, UCC plans to enhance its technological infrastructure, connectivity, and instructional platforms to facilitate effective teaching and learning experiences. Quality Assurance and Accreditation: UCC intends to institutionalize a dedicated Quality Assurance and Accreditation Unit, ensuring continuous improvement and compliance with quality standards. UCC@APPS (2022-2027 Administrative Agenda) Phase 1 Milestones (SY 2022-2023) Accreditation and Regulatory Bodies Visit: The BECEd program received level 2 - five years accreditation status and was invited for level 3. The BSN program received level 3 - five years accreditation status and was invited for level 4. The BSA program received commendation during its visit by the Board of Accountancy (BOA) in March 2023. Internationalization and Partnerships: UCC research has been accepted for presentation in India at the SLAN conference on July 19-21, 2023. Finalization of the Memorandum of Agreement (MOA) with Chonburi Technological College, Thailand. Scheduled MOA signing and research presentation at STIKES, Bali Indonesia on June 18-21, 2023. Benchmarking and partnership MOA signing with research presentation in Korea on July 24-28, 2023. MOU forged with SEAMEO INNOTECH on February 14, 2023. Library Consortium established with North Luzon Adventist College (NLAC). Licensure Examination: Nursing Licensure Examination: May 2022: UCC achieved a 100% passing rate. November 2022: UCC achieved a 75.86% passing rate. Licensure Examination for Teachers (March 2023): BSEd: UCC achieved an 85.71% passing rate. BEEd: UCC achieved a 66.67% passing rate. Instructional Program: Subscription to Quipper (LMS) for the Senior High School. Implementation of the Certificate of Teaching and Teaching in Filipino Programs. SEAMEO INNOTECH micro-credential training for UCC Graduate School. Research: Expanded research engagements through ASCENDENS MOA, including research conferences, publications, and partnerships. Creation of an online repository for student thesis research. Empowered academic departments in research programs. 80% of research by students and faculty published in the ASCENDENS Journal. Internationalization of research programs through publication in international research journals and collaborations with other institutions. Conclusion: Union Christian College has showcased remarkable progress in the face of challenges, demonstrating its commitment to academic excellence, research, and community engagement. As UCC embarks on its 2022-2027 administrative term, the outlined goals and initiatives provide a strong foundation for sustained growth, program expansion, technological advancement, and global outreach. By aligning its agenda with the UCC @APPS framework, the institution aims to solidify its identity, heritage, and spirituality while becoming a prominent symbol of the church’s educational ministry.